1996
DOI: 10.1080/095530096145850
|View full text |Cite
|
Sign up to set email alerts
|

Increased micronucleus frequency in the progeny of irradiated Chinese hamster cells

Abstract: V79 Chinese hamster cells were irradiated with doses of 1-12 Gy 300 kV X-rays. Their colony-forming ability and the frequency of micronuclei in binucleate cells after treatment with cytochalasin B was determined at various times after irradiation. The frequency of micronuclei determined within the first 24 h after irradiation increased with doses up to 4 Gy and decreased as the dose increased further. Up to 4 Gy there was a close correlation between surviving fraction and the fraction of cells without micronuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…These findings are in good agreement with the earlier studies. [35,36] It has been observed with MN as well as comet assay that the menace of the radiation-induced genomic instability is reduced in the presence of RUT and QRT. Damage to DNA was attested by increased OTM with increasing doses of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in good agreement with the earlier studies. [35,36] It has been observed with MN as well as comet assay that the menace of the radiation-induced genomic instability is reduced in the presence of RUT and QRT. Damage to DNA was attested by increased OTM with increasing doses of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a good quantitative inverse relationship between micronucleus frequency and clonogenic survival (Wandl et al, 1989;Jamali and Trott, 1996;Mariya et al, 1997); however, there are also several reports in which such a correlation was not found (Bush and McMillan, 1993;Slavotinek et al, 1993;Villa et al, 1994). Some authors have reported an inverse correlation between apoptotic frequency and cell survival (Radford and Murphy, 1994;Olive and Durand, 1997;Guo et al, 1999), whereas others found no correlation (Yangihara et al, 1995;McKenna et al, 1996).…”
mentioning
confidence: 89%
“…This irradiation-induced genome instability is characterized by a high frequency of chromosomal and gene mutations, an increased number of micronuclei, increased micro-and minisatellite variability, increased malignant transformations, and increased clonal heterogeneity. In these cells high rates of gene amplification and disturbance of cell differentiation were also observed (KRONENBERG, 1994;LOEB, 1994;MORGAN et al, 1996;LITLLE, 1998;JAMALI, ROTT, 1996;MEYN, 1997;TROTT, TEIBE, 1998;LIMOLI et al, 1999).…”
Section: Discussionmentioning
confidence: 94%